PERAN SALURAN DISTRIBUSI DALAM MENINGKATKAN VOLUME PENJUALAN PADA TOKO SINAR ANEKA SORONG PAPUA BARAT DAYA - Muh. Arif; Andi Sismar (Jurnal Bisnis dan Kewirausahaan, 2024)
Distribution channels play a key role in increasing the sales volume of a product or service. Distribution channels involve a series of steps that involve the movement of products from the manufacturer to the consumer. By understanding and managing distribution channels effectively, companies can optimize the sales potential of their products and achieve greater profits. This research aims to determine the role of distribution channels in increasing sales volume. The type of research used is quantitative descriptive, where the author describes the results of observations and analyzes data obtained in the field. Data is analyzed using simple regression analysis methods. The analysis results show that distribution channels have a significant impact on sales volume.